A three-dimensional reconstruction of coal microstructure using the Cryo-FIB-SEM technique. (1st September 2020) - Zakrzewski, Marcin; Schertel, Andreas; Brus, Grzegorz; Wagner, Marian; Sciazko, Anna; Komatsu, Yosuke; Kimijima, Shinji; Kaneko, Shozo; Szmyd, Janusz S.
Graphical abstract: Highlights: A 3D digital reconstruction of xylo-detritic lignite microstructure was obtained. Coal microstructure was observed at cryogenic temperatures to avoid drying artifacts. Lignite compounds were identified based on their morphological features. Abstract: Two basic homogeneous lithotypes, defined as elementary coal layers, within the seam of lignite can be distinguished: xylitic and detritic coal. As each of them exhibits various features, including structure, mechanical, technological properties, and chemical ash composition, the share of lithotypes within a lignite deposit provides important information regarding the applicability of this fuel. This study describes a unique three-dimensional reconstruction of a lignite microstructure using scanning electron microscopy (SEM) to acquire images of subsequent coal cross-sections which are exposed by focused ion beam (FIB) milling at cryogenic temperatures. Because of the organic origin and high moisture content, the fully hydrated lignite sample was frozen in nitrogen slush for the SEM observation in its frozen native state in order to avoid dehydration and other sample modifications. The acquired data cube contained distinguished petrographic phases, identified with coaly macerals of xylitic and detritic coal along with the fragment of the gelified leaf tissue, typical for ortho-lignite structure. The 3D reconstruction and phase segmentation process was performed using the Avizo software to constitute a cuboid model with an edge length of ca. 10 µm. Lignite exhibits low local uniformity, therefore to draw generally valid conclusions, a statistical relevant number of similar three dimensional reconstructions at representative locations for the different lithotypical and petrographic coal compositions within the analysed fragment would be demanded.